PENGARUH FUNDAMENTAL RENANG TERHADAP HASIL BELAJAR KETERAMPILAN GERAK DASAR RENANG SISWA KELAS IV SD NEGERI MANTINGAN - Mohammad Arif Eka Prastiya; Togik hidayat; Mohammad Fatoni (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Swimming is a water sport that requires qualified swimming fundamentals. students can do the desired swimming skills. In class IV Elementary School students must understand about the basics of swimming. A stage of development of spicomotor in class IV students starting at the age of 10 years is a continuation of the development of their thinking. This study uses an experiment with True Experimental Design with sampling techniques using pretest-posttest. From this study the results of the pre-test obtained from eleven students concluded that the level of basic swimming motion skills average percentage of eleven students was 95% and were in the high category. Based on the results of the post test on the eleven students it can be concluded that the average percentage of the six students is 25% and is in the low category. Then it can be concluded that researchers conduct research on skating skills and breathing techniques to help improve their skills.